1995
DOI: 10.1007/bf00184087
|View full text |Cite
|
Sign up to set email alerts
|

Explorative study of interleukin levels in the human cornea

Abstract: Keratitis, keratoconus with inflammatory signs, and ulcerating processes showed higher interleukin levels than corneas with non-inflammatory disorders like scar formation, corneal dystrophy and keratoconus. The results could show that, depending on the clinical diagnosis, the inflammatory status of the cornea may be evaluated by the interleukin levels determined in the corneal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 15 publications
1
23
0
3
Order By: Relevance
“…Further studies have observed high IL-8 and IL-1 rates in corneas after eye burns [53]. These data could be reproduced in the EVEIT system with IL-8 being upregulated for NaOH and also for the sodium lauryl sulfate (SLS) (Fig.…”
Section: Release Of Inflammatory Mediatorsmentioning
confidence: 78%
“…Further studies have observed high IL-8 and IL-1 rates in corneas after eye burns [53]. These data could be reproduced in the EVEIT system with IL-8 being upregulated for NaOH and also for the sodium lauryl sulfate (SLS) (Fig.…”
Section: Release Of Inflammatory Mediatorsmentioning
confidence: 78%
“…44 The latter is of interest, given that individuals of Asian descent are more susceptible to developing KC than Caucasians. 45 Indeed, KC corneas have increased IL-1α and IL-1β expression, 35,46,47 and fibroblasts from KC patients show elevated expression for IL-1α receptors. 48 In general, IL-1α is upregulated during corneal trauma and inflammation.…”
Section: Interleukin-1mentioning
confidence: 98%
“…Ophthalmic Res 2006;38:182-188 183 logical processes, such as ocular rosacea, bullous keratopathy, keratitis, keratoconus, alkali burn, corneal ulceration, vernal keratoconjunctivitis, ocular pemphigoid, keratoconjunctivitis sicca, contact lens wear and uveitis, and also in the pathogenesis of corneal graft rejection [2,3,[5][6][7][8][9][10][11][12][13][14][15] . IL-6 may also play a crucial role in the development of postoperative infl ammation after cataract surgery [16] , since it has been shown to stimulate collagen synthesis and may therefore be involved in corneal wound healing [9,10,17] .…”
Section: Enhanced Release Of Il-6 and Il-8 Into Tearsmentioning
confidence: 99%